Process Evaluation of a Randomised Controlled Trial for TeleClinical Care, a Smartphone-App Based Model of Care - Indraratna, Praveen; Biswas, Uzzal; Liu, Hueiming; Redmond, Stephen J.; Yu, Jennifer; Lovell, Nigel H.; Ooi, Sze-Yuan (Frontiers in Medicine, 2022)
Background: A smartphone app-based model of care (TeleClinical Care – TCC) for patients with acute coronary syndrome (ACS) and heart failure (HF) was evaluated in a two-site, randomized control trial of 164 participants in Sydney, Australia. It included a telemonitoring system whereby abnormal blood pressure, weight and heart rate readings were monitored by a central team, who referred clinically significant alerts to the patients’ usual healthcare provider(s). While the primary endpoint, 30-day readmissions, was neutral, intervention arm participants demonstrated improvements in readmissions over six months, cardiac rehabilitation (CR) completion and medication compliance. A process evaluation was designed to identify contextual factors and mechanisms that influenced the results, as well as strategies of improving recruitment and delivery of the intervention, for a planned multicentre trial of over 1000 patients (TCC-Cardiac). Methods: Multiple data sources were used, including interviews with four TCC team members, three GPs and three cardiologists. CR completion rates, HF outreach service (HFOS) referrals and cardiologist follow-up appointments were audited. A patient questionnaire was analysed for evidence of improved self-care as a hypothesized mechanism of benefit. An implementation research logic model was used to synthesize our findings. Results: Rates of HFOS referral (83% vs. 72%) and cardiologist follow-up (96% vs. 93%) were similarly high in the intervention and control arms, respectively. Team members were largely positive towards their orientation and training, but highlighted several strategies that could be optimized for TCC-Cardiac: streamlining of enrolment, screening patients in non-cardiac wards, and ensuring team members had adequate recruiting time (>15 hours per week). GPs and cardiologists viewed the intervention favourably regarding potential benefit of responding to abnormalities for patients, though there were concerns of the potential additional workload generated by insignificant alerts. Clear delineation of which clinician was primarily responsible was also recommended, as well as a preference to receive regular summary data. Several patients commented on the mechanisms of improved self-management because of TCC, which possibly led to improved medication compliance. Discussion: TCC was associated with several benefits. The conduct and delivery of TCC-Cardiac will be improved by the findings of this process evaluation.